Strategies for Implementing Digital Governance for Smart City Development - Hastuti, Hesti (Asian Digital Governance Problems, 2025)
Purpose: This study aims to analyze the implementation strategies of digital governance in supporting Smart City development in Makassar City during 2025. Subjects and Methods: The study employed a quantitative descriptive-explanatory approach involving 200 respondents consisting of government officials, Smart City implementers, technical staff, academics, and community members. Data were collected using structured questionnaires and analyzed using descriptive statistics and multiple linear regression analysis with SPSS version 26. Results: The findings indicate that corporate strategy, program strategy, resource support strategy, and institutional strategy significantly influenced digital governance effectiveness. Program strategy emerged as the most dominant factor affecting Smart City governance performance. Digital governance implementation improved service efficiency, transparency, responsiveness, and accessibility through integrated digital public services and Smart City applications. Institutional coordination and organizational adaptability remained important challenges affecting governance sustainability. Conclusions: Effective digital governance in Makassar City depends on the integration of technological innovation, strategic governance, institutional strengthening, and inclusive citizen participation to support sustainable and responsive Smart City development.